PHYSICOCHEMICAL CHARACTERISTICS AND AMENABILITY TO BENCH SCALE TREATMENTS OF SOME INDUSTRIAL EFFLUENTS AND SEDIMENTS IN LAGOS METROPOLIS (2014)
Untreated industrial effluents discharged into land and surface water are of great environmental concern. Previous studies on physicochemical characteristics of effluents and sediments from discharged points of various industrial sectors in Lagos metropolis are inadequate in scope, duration, chemical treatment options and estimated pollutant discharge load which are of importance in waste water management. This study was designed to investigate the physicochemical characteristics of effluents and sediments from industrial estates in Lagos metropolis, to estimate pollutant loads and determine appropriate chemical treatment options. Effluents (75) and sediments (72) were sampled once in two months from the discharge points of textile, pharmaceutical, food and beverages, basic metals and paint industries from November 2006 to May 2008. Total Dissolved Solids (TDS), pH, alkalinity, total hardness, sulphate, phosphate, nitrate, chloride, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD)] and heavy metals were determined in the effluents according to APHA methods and compared with National Environmental Standards and Regulations Enforcement Agency (NESREA) limits. Organic carbon, pH and heavy metals were also analysed in the sediments. Multiple Linear Regression (MLR) was used to estimate organic load and eutrophication potential. Industrial effluent with the highest level of pollutant load was subjected to bench scale treatments using ferrous chloride, ferrous sulphate, Fenton’s reagent, alum, and activated carbon separately. Efficiency of treatment was ascertained by determination of TDS and COD. The Pearson correlation at p = 0.05 was used to establish the significance between the levels of metals in the effluents and sediments.. Physicochemical characteristics (mg/L) of effluents from textile and pharmaceutical industries were 1160±890 and 630±260 for TDS, 316±280 and 230±97 for alkalinity, 60±32.and 53±44.for total hardness, 156±73 and 34±36 for sulphate, 1.0±0.3 and 0.7±0.6 for phosphate, 60.0±40.0 and 75±45 for nitrate, 65±19 and 61±40 for chloride, 1.8±1.7 and 1.3±1.2 for DO, 209±72 and 150±96 for BOD, 343±130 and 245±140 for COD, 0.7±0.3 and 0.5±0.2 for Zn, 1.5±1.0 and 0.3±1.1 for Cu, 2.5±0.3, 0.03±0.03 for Cr and corresponding pH was 10.6±1.1 and 5.5±1.2 respectively. Effluents from foods and beverages, basic metal and paint industries had lower levels of TDS, alkalinity, phosphate, and chloride. Nitrate, DO, BOD, and COD levels exceeded NESREA limits for all effluents. The pH and organic carbon UNIVERSITY OF IBADAN LIBRARY iv ranged from 4.2-7.5 and 0.2-4.5% respectively for the sediments with the levels (μg/g) of Zn, Cr and Cu ranged from 196-3270, 7-49 and 21-244 respectively. Metal levels in sediments were higher than in effluent. Significant correlations were observed for Zn (0.64) and Cr (0.75) between effluents and sediments. The linear regression coefficients for organic load and eutrophication modelling ranged from 0.638-0.999 and 0.301-0.999 respectively. Efficiency of treatment options for COD reduction was in the order: Fenton’s reagent (90%) > ferrous chloride (87%) > ferrous sulphate (66%) > alum (61%) > activated carbon (47%) while significant TDS reduction was not achieved. Industrial effluents and related sediments in Lagos metropolis were highly polluted. Applications of Fenton’s reagent and ferrous chloride were the appropriate chemical treatment options for organic pollutants in textile effluent. Keywords: Industrial effluent and sediment, Heavy metal pollution, Lagos metropolis, Pollutant discharge load. . Word count: 496